2014
DOI: 10.1002/hup.2418
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of auditory deviance detection by acute nicotine is baseline and deviant dependent in healthy nonsmokers: a mismatch negativity study

Abstract: These findings provide preliminary support for the role of nicotinic neurotransmission in sensory memory processing of auditory change and suggest that nicotinic receptor modulation can both enhance and diminish change detection, depending on baseline MMN and its eliciting stimulus feature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 135 publications
(169 reference statements)
4
16
0
Order By: Relevance
“…In general, the findings parallel our earlier report of the dual actions of the broad spectrum nAChR agonist, nicotine, on MMN in groups of healthy surrogates exhibiting relatively compromised and efficient deviance detection (Knott et al 2014). Increases in auditory change detection in individuals with diminished MMNs are of particular importance for SZ.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In general, the findings parallel our earlier report of the dual actions of the broad spectrum nAChR agonist, nicotine, on MMN in groups of healthy surrogates exhibiting relatively compromised and efficient deviance detection (Knott et al 2014). Increases in auditory change detection in individuals with diminished MMNs are of particular importance for SZ.…”
Section: Discussionsupporting
confidence: 86%
“…In line with previous suggestions of an inverted U-shaped response characterizing cognitive effects of nicotinic stimulation (Newhouse et al 2004), and based on our recent study with the prototypical nAChR agonist, nicotine, which enhanced auditory deviance detection in individuals with small amplitude MMNs and attenuated deviance detection in those with higher amplitude MMNs (Knott et al 2014), we hypothesized that both doses of CDP-choline (vs. placebo) would increase deviance detection (MMN) in individuals exhibiting relatively diminished detection ability (i.e. low baseline MMN amplitudes) and exert negative or diminishing effects in those with relatively moderate, optimal, or above optimal detection ability (i.e., medium or high baseline MMN amplitudes).…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…In humans, cholinergic manipulation affects auditory novelty detection (Klinkenberg, Blokland, Riedel, & Sambeth, 2013;Knott et al, 2014;Moran et al, 2013). Likewise, diverse studies in animals support the notion that ACh release is necessary for the induction of auditory plasticity (Bjordahl, Dimyan, & Weinberger, 1998;Edeline, 2012;Leach, Nodal, Cordery, King, & Bajo, 2013;Metherate & Weinberger, 1989).…”
Section: Effect Of Cholinergic Modulation On Ssamentioning
confidence: 92%
“…Schizophrenia has been associated with alterations in neurotransmission as the one mediated by the NMDA (N-methyl-d-aspartate) receptor (Matsuno et al, 2015). Moreover, several studies have showed that acoustic MMN is sensitive to cholinergic modulation (Dunbar et al, 2007;Knott et al, 2014;Mathalon et al, 2014;Moran, Campo, Symmonds, Stephan, Dolan, & Friston, 2013) or to nitrous oxide (N 2 O) (e.g., Pang & Fowler, 1999). In autism spectrum disorders, larger amplitudes and earlier latencies relative to control subjects have been observed in children and adults diagnosed with these disorders (Kujala et al, 2007;Lepisto et al, 2008).…”
Section: Overviewmentioning
confidence: 96%